Instrumenty controllingu operacyjnego stosowane w przedsiębiorstwach województwa warmińsko-mazurskiego - Dynowska, Joanna (The Use of Operational Controlling Tools as Applied to Enterprises within the Region of Warmia and Mazury, 2007)
The use of particular instruments of operational controlling enables managers to make proper decisions and control their departments and processes in order to achieve their goals. According to the survey, which was carried out among 169 firms with the employment of over 50 workers, instruments of operational controlling are not well-known among managers. Only a small per cent of respondents use the instruments in practice. The most popular tools of operational controlling used were: the break ever, point analysis, the purchase order quantity analysis and the short-term cost account. Relatively low tee controlling tools can be attributed to the use of traditional cost accounting methods. In order to use controlling techniques, companies need to adopt modern cost accounting techniques such as variable cost accounting or activity-based costing.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1174, s. 138-145